Palinología de angiospermas de la Formación Monte Chico (Cretácico superior) de la provincia de Santa Cruz, Argentina - Povilauskas, Leticia Karina (2013)
Diverse palynological assemblages composed by both continental and marine palynomorphs were recovered from the Monte Chico Formation, Upper Cretaceous, Santa Cruz Province. In this contribution palynological assemblages were studied, and the samples were taken from the entire section of this unit. Fifty fi ve species of angiosperm pollen grains were determined. They belong to the genera: Arecipites, Beaupreaidites, Clavamonocolpites, Clavatricolpites, Ericipites, Forcipites, Haloragacidites, Ilexpollenites, Liliacidites, Longapertites, Nothofagidites, Peninsulapollis, Periporopollenites, Proteacidites, Pseudowinterapollis, Psilatricolpites, Psilatricolporites, Quadraplanus, Rhoipites, Rousea, Senipites, Sparganiaceapollenites, Spinizonocolpites, Triatriopollenites, Tricolpites, Tricolporites and Triporopollenites. On the basis of the stratigraphic distribution of the identifi ed species, mainly in Argentina and Antarctica, and together with the preliminary analysis of spores, a Maastrichtian-Late Maastrichtian age is here suggested. The palynological assemblages obtained would typically indicate a near shore marine environment of deposition, with marginal conditions towards to the upper section.